Effect of Sowing Date and Nitrogen Rates on Morphometric Features and Photosynthetic Performance in Sugar Beet - Beata Michalska-Klimczak; Grażyna Mastalerczuk; Zdzisław Wyszyński; Vladimír Pačuta; Marek Rašovský (Agriculture)
Sugar beet is a critical crop for global sugar production, and optimizing its growth and yield requires a thorough understanding of the effects of agronomic practices such as sowing date and nitrogen fertilization. This study was conducted in the WULS-SGGW Experimental Field in Miedniewice, Poland, during two growing seasons. The aim of the research was to determine the impact of sowing dates and nitrogen fertilization on the morphometric features and photosynthetic performance of the Lubelska sugar beet variety grown in Luvisols soil. The experiments were arranged as split-plot designs (SPDs) with four replications. The factors of the experiment were the sowing date (optimal and delayed by two weeks) and nitrogen fertilization at doses of 0, 60, and 120 kg N·ha−1. The photosynthetic activity of sugar beet plants was measured four times during the growing season using chlorophyll fluorescence (ChlF) parameters. Morphometric features were determined by collecting sugar beet plants after each chlorophyll fluorescence measurement. The obtained results demonstrate the significant effect of nitrogen doses on the morphometric parameters of aboveground biomass. Increasing nitrogen doses also differentiated chlorophyll fluorescence parameters, such as FV/F0, FV/FM, PIABS, ET0/CS0, and ET0/CSM. A two-week delay in sowing affected both the fluorescence parameters and morphometric features of sugar beet, highlighting the interaction between agronomic practices and plant physiology.